Penyuluhan Hukum Keluarga Islam Berbasis Maqasid al-Syari ‘ah tentang Peran Istri dalam Membangun Ketahanan Keluarga Pasca Pandemi Covid-19 Bagi Ibu Muda Fatayat NU Kabupaten Sidoarjo - Ratna Suraiya; Nashrun Jauhari; Niswatin Niswatin; Taseman Taseman; Resty Rahmatika (Universitas Nurul Jadid, 2024)
From 2020 to 2022, Sidoarjo Regency has identified a surge in family conflicts triggered by wives' protests. Evidence includes an increase in divorce filings, child neglect, and internal family conflicts due to frustration. Therefore, it is necessary to educate the community through outreach activities on building family resilience, emphasizing the role of the wife in the family. Islamic family law based on maqasid al-Shari'ah was chosen as the outreach material because it is relevant and more acceptable to the wives in Sidoarjo Regency, the majority of whom are Muslims. The organized young mothers of Fatayat NU were selected as the target audience. The service method used was service learning, an approach that combines academic teaching with finding appropriate problem-solving solutions for the community. The results of this community service showed an increase in understanding among the young mothers of Fatayat NU in Sidoarjo Regency about strategies for building family resilience through the role of the wife post-pandemic, based on the concept of Islamic family law rooted in maqasid al-Shari'ah.